The Implementation of ICT in Teaching English as Foreign Language: A Case Study of Premary School English Teachers in Kotamobagu, North Sulawesi - Dewi Christa Kobis; Michel Farrel Tomatala (STBA LIA - Jakarta, 2020)
This study aims to find out whether ICTs (Information and Communication Technologies) really helps EFL teachers in Kotamobagu to improve their students’ English ability. This study uses the teachers’ perceptions as the main sources to answer the research questions of this current study. It focuses on finding the EFL teachers’ knowledge level in implementing ICTs, the level of ICT implementation for educational purposes, and problems that teachers might face during ICT implementation in the classrooms. This study uses mixed method of quantitative and qualitative approach by using questionnaire and interview to gain the data. The findings show that in general, teachers have fair capability in using ICTs. They also have positive attitude towards ICT implementation where they claimed that ICTs are useful to improve students’ learning achievement. The teachers use ICTs for various reasons and at the last this study found that lack of ICT facilities has become the main problem that they often face.